Deformation of Ordered Mesoporous Silica Structures on Exposure to High Temperatures. (15th September 2014) - Lowe, John B.; Baker, Richard T.
Abstract : Ordered mesoporous silica materials are of interest for a wide range of applications. In many of these, elevated temperatures are used either in the preparation of the material or during its use. Therefore, an understanding of the effect of high temperature treatments on these materials is desirable. In this work, a detailed structural study is performed on silicas with three representative pore structures: a 2-D hexagonal pore arrangement (SBA-15), a continuous 3D cubic bimodal pore structure (KIT-6), and a 3D large cage pore structure (FDU-12). Each silica is studied as prepared and after treatment at a series of temperatures between 300 and 900°C. Pore structures are imaged using Transmission Electron Microscopy. This technique is used in conjunction with Small-Angle X-ray Diffraction, gas physisorption, and 29 Si solid state Nuclear Magnetic Resonance. Using these techniques, the pore size distributions, the unit cell dimensions of the mesoporous structures, and the relative occupancy of the distinct chemical environments of Si within them are cross correlated for the three silicas and their evolution with treatment temperature is elucidated. The physical and chemical properties before, during, and after collapse of these structures at high temperatures are described as are the differences in behavior between the three silica structures.